Improved Bounds on the Size of Separating Hash Families of Short Length: Penying Rochanakul - Team, Support (Thai Journal of Mathematics, 2020)
In this paper, we present some new upper bounds on the size of separating hash families of type w1,w2 of short length, where the length N is not exceeding 2w2. A new proof for tight bounds on the size of separating hash families of type 1, w is also given.